Advances in Computer Entertainment 10th International Conference, ACE 2013, Boekelo, The Netherlands, November 12-15, 2013. Proceedings - Reidsma, Dennis; Katayose, Haruhiro; Nijholt, Anton; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the refereed conference proceedings of the 10th International Conference on Advances in Computer Entertainment, ACE 2013, held in Boekelo, The Netherlands, in November 2013. The 19 full paper and 16 short papers presented together 42 extended abstracts were carefully reviewed and selected from a total of 133 submissions in all categories. The papers cover topics across a wide spectrum of disciplines including new devices; evaluation and user studies; games as interface to serious applications; creating immersion; interfaces; new experiences; procedural approaches and AI; and theory. Focusing on all areas related to interactive entertainment they aim at stimulating discussion in the development of new and compelling entertainment computing and interactive art concepts and applications.
New devices -- Evaluation and user studies -- Games as interface to serious applications -- Creating immersion -- Interfaces -- New experiences -- Procedural approaches and AI -- Theory.
Keywords: Computer science; Computer communication systems; Algorithms; User interfaces (Computer systems).; Artificial intelligence; Computer graphics; Computer Science; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Computer Imaging, Vision, Pattern Recognition and Graphics; Algorithm Analysis and Problem Complexity; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Electronic books